Miskonsepsi guru sekolah dasar pada konsep bunyi - Anatri Desstya; Fitri April Yanti; Anip Dwi Saputro (AL-ASASIYYA: Journal Of Basic Education, 2020)
Elementary school teachers are one of the sources of student’s misconceptions, so their understanding needs to be identified. However, the process of identifying the understanding of the concept of science is still small and only on certain materia. This study was aimed to investigate elementary school teacher's understanding of sound concepts. This study uses a qualitative approach with descriptive type. The research data are sourced from elementary school teachers' answers to questions about the concept of high and low sounds, in the form of a teacher's justification for the statement of questions presented along with the discussion. The population was all grade 4 elementary school teachers in Surakarta (120 teacher), the sample of 30 teachers from public and private elementary schools, the status accreditation A and B, with a purposive random sampling technique. The sample taken consisted of teachers in the age range of 30 to 60 years, 11 male teachers and 19 female teachers, and 50% were certified educators. Data collection techniques are carried out by providing diagnostic tests of misconceptions on the subject of the concept of high and low sounds. Data analysis technique refers to the category of concept understanding formulated by Tuysuz (2009), which is understanding, misconception, not understanding, and guessing. The results showed that in understanding the concept of high and low sounds 1.11% of teachers understood the concept well, 71.11% of teachers did not understand the concept, 26.67% of teachers experienced misconceptions, and 1.11% of teachers guessed.